EVALUATION OF PATHOLOGICAL COMPLETE RESPONSE FOLLOWING NEO ADJUVANT CHEMOTHERAPY IN BREAST CANCER PATIENTS - Chiragh, Sadaf; Bilal Ahmad; Rahimullah Khattak; Sohail Ahmad; Abdullah Khanzada (Journal of Postgraduate Medical Institute, 2023)
Objectives: To evaluate the rate of pathologic complete response (pCR) in patients with breast carcinoma who received neoadjuvant chemotherapy. Methodology: The following cross sectional study was conducted at the Department of Oncology, Hayatabad medical complex from December 2022 to May 2023 comprising of 174 patients aged between 30-70 years. Keeping inclusion and exclusion criteria in perspective sampling was done through non-probability consecutive sampling technique. The primary outcome measured was the complete pathological response (pCR), which was assessed based on four categories: stage and lymph node, molecular signature, chemotherapy regimen, and age. Data analysis was achieved using SPSS version 23.0 and results were depicted in the form of description, tables and graphs. Results: Out of 174 patients, 27 patients achieved a pathologic complete response (pCR). Among the patients classified based on stage and lymph node involvement, the highest number (n= 25, 31.6%) of pCR cases was observed in the stage II lymph node-negative group. The study also analyzed pCR rates based on the molecular signature. The triple-negative subtype exhibited the top pCR rate of 26 %. Furthermore, the study assessed pCR rates based on different chemotherapy regimens. The maximum pCR rate was observed in patients receiving TCHP (20%). Among the patients based on age, those aged less than 35 years had the highest pCR rate (100%). Conclusion: The propensity of neo-adjuvant chemotherapy (NACT) to convert an in-operable tumor into an operable one is unprecedented. This allows conservative surgery to take place with reduced morbidity and mortality among cancer patients.